FABRICATION AND PROCESS PARAMETER OPTIMIZATION OFA 3D PRINTER USING RESPONSE SURFACE METHODOLOGY - Joti, Joytun Nisa; Ahmed, Rumaisa; Ishraq, Fatin (My University, 2019)
3D printing or additive manufacturing is a technology in which 3D objects are printed by depositing a thin layer of material layer-by-layer until a final product is produced. In this thesis work, it has been focused on the Fabrication of a Portable 3D Printer for the manufacturing of sample parts by using Fused Deposition Modelling (FDM) process. After fabricating the 3D printer, the primary process parameters such as nozzle temperature, extrusion speed and fill density in addition to their interactions are studied. It has been observed that these process parameters influence the dimensional accuracy & extrusion time of the part produced by the process of Fused Deposition Modelling (FDM). The main objective of the thesis work is to create a reliable and cost efficient 3-D printer and to minimize the dimensional variation that usually occurs to plastic parts produced by 3D printers. Cartesian mechanism has been used where the print bed moves in the Z direction and the extruder moves in both the X & Y directions. To increase the performance and printing accuracy of the 3D printer, a Bowden type extruder has been used. The 3D printing filament that has been used is made of Polylactic acid or polylactide (PLA, Poly) which is biodegradable thermoplastic aliphatic polyester derived from renewable resources. The process involved 3D solid modeling to design, 3D printing with coated adhesive applied on the printing platform, measurement of dimensional variation of the printed parts and statistical analysis. Experiments are conducted using full factorial central composite design. Response surface methodology based desirability analysis has been employed for optimization of FDM process parameters namely, nozzle temperature, extrusion speed and fill density. Mathematical models were developed and tested for accuracy & extrusion time using Design Expert 11 software for RSM application.
FABRICATION AND PROCESS PARAMETER OPTIMIZATION OF A 3D PRINTER USING RESPONSE SURFACE METHODOLOGY